Advancements and future prospects of adeno-associated virus-mediated gene therapy for sensorineural hearing loss - Li, Linke; Shen, Tian; Liu, Shixi; Qi, Jieyu; Zhao, Yu (Frontiers in Neuroscience, 2024)
Sensorineural hearing loss (SNHL), a highly prevalent sensory impairment, results from a multifaceted interaction of genetic and environmental factors. As we continually gain insights into the molecular basis of auditory development and the growing compendium of deafness genes identified, research on gene therapy for SNHL has significantly deepened. Adeno-associated virus (AAV), considered a relatively secure vector for gene therapy in clinical trials, can deliver various transgenes based on gene therapy strategies such as gene replacement, gene silencing, gene editing, or gene addition to alleviate diverse types of SNHL. This review delved into the preclinical advances in AAV-based gene therapy for SNHL, spanning hereditary and acquired types. Particular focus is placed on the dual-AAV construction method and its application, the vector delivery route of mouse inner ear models (local, systemic, fetal, and cerebrospinal fluid administration), and the significant considerations in transforming from AAV-based animal model inner ear gene therapy to clinical implementation.